Analysis of SNS popularity from different perspectives among users - Shaikh, Muniba; Dar, Humaira; Shah, Asadullah (2013)
Social networking is unquestionably one of the most vital and influential aspect of today’s society. A great number of Social Networks (SNs) are available now a days and being used by the people all around the globe. This paper provides an analysis of four most popular interactive SNs that are, Facebook, LinkedIn, Twitter and MySpace according to different perspectives. The data has been collected from secondary sources that has been used in this paper. The data has been analyzed and compared by four different perspectives based on user traffic, age, gender, and education of the users. The analysis of data indicate some useful and new insights such as the Facebook is the most popular network having the highest number of users. LinkedIn network, in the age groups between 34 to 45 years having the highest number of users. Interestingly LinkedIn, for gender base analysis, for the age groups of 34-45, numbered less than male users. This indicate that male professional out number than female users for the same age groups (34-45). Overall findings show that female users are 66% and rest 34% are male users for all four social networks that were analyzed in this research work.